(untitled) (Journal of Enam Medical College, 2023)
Renal cell carcinoma (RCC) usually metastasizes to lung, liver, bone and brain. We report a case of an elderly man who underwent radical nephrectomy for renal cell carcinoma and developed a metastasis in the plane between contralateral psoas muscle and quadratus lumborum muscle 11 years after the operation J Enam Med Col 2021; 11(1): 52-54